Application of Tire Pyrolysis Oil as an Alternative Fuel for Internal Combustion Engines—A Literature Review - Keji Qi; Xuehui Gan (Journal of Combustion)
Tire pyrolysis oil (TPO) has been recently used as an alternative to conventional fuels for internal combustion (IC) engines in order to satisfy some environmental and economic concerns. The main focus of this review is to shed light on the importance of TPO as an alternative fuel for IC engines. This paper systematically describes the TPO productions, composition, properties, and application methods in IC engines, such as binary blend, ternary blend, dual fuel mode, and spark ignition (SI) mode. The results indicate that blending TPO in diesel fuel deteriorates the engine performance and emissions, which can be improved by adding biofuels or nanoparticles. Dual fuel mode is a promising method to enhance the overall fuel quality and reduce nitrogen oxide (NOx) emissions. TPO blended with alcohols can serve as fuel in SI engines and the ratio of TPO is less than 25 vol.%. The TPO–diesel blend had better performance at each test engine load in terms of energy, exergy, and sustainability when the ratio of TPO is 10 vol.%. In conclusion, it can be said that TPO is an important factor from the viewpoint of both waste management and the protection of fossil fuel resource depletion.